A Study of The Relationship between Use of Bilingual Strategies and Academic Performance of Assumption University’s Learners of French - Benassaya, Romain (Scholar: Human Sciences, 2017)
This study examines the relationship between students’ use of bilingual strategies and their academic performance in the Department of Business French of Assumption University (AU). A quantitative approach was adopted. The study includes a sample of 63 students learning French in AU. A questionnaire was elaborated to collect data about the frequency of use of bilingual strategies and the academic performance of students. Descriptive and correlational statistics, including a Pearson Product Moment computation of correlation, were used to interpret the data and measure the significance of the correlation between the two sets of variables. The results indicated that a high frequency of use of bilingual strategies is correlated with high academic performances. Some recommendations grounded in the results are proposed in conclusion.